Students' Viewpoints Toward Part of Speech as the Fulcrum of Grammar - Hustiana (Journal of English and Education (JEE), 2023)
This study concerned with students’ viewpoints toward part of speech which attempted to figure out the students’ viewpoints about parts of speech, to explore students’ problems in learning parts of speech, and to reveal the students’ strategies to be acquainted with part of speech. This research was a qualitative study where the data were collected by interview. The subjects of this research were 28 students (15 females and 13 males) in the third semester, English Education Department at Faculty of Training and Education of a State University in West Sulawesi who were chosen randomly. All of the students were interviewed about their viewpoints about parts of speech. Based on the result of the research, the researcher found that some students misunderstood the definition of part of speech, and some of them understand it. The students were found to have problems in learning parts of speech such as being less practice, not mastering the parts of speech well, lack of vocabulary, and inability to differentiate parts of speech, as well as lack of understanding. In the mean time, the students’ way to become familiar with parts of speech was by memorizing the word classes, knowing the characteristics of the word, paying attention to the position of the word in a sentence, knowing the meaning of the word, guessing the word, and looking at the word before and after in a sentence or text. The result of the study could be useful for future lectures about parts of speech.